Effects of Instructor Gender, Visual, and Auditory Melodic Recorded Instruction on Sequential Working Memory Recall in Individuals with and without Autism Spectrum Disorder - Schwartzberg, Edward Todd; Silverman, Michael J (Voices: A World Forum for Music Therapy, 2019)
There is a lack of empirical inquiry concerning the effect of the therapist’s gender and aspects of visual and auditory melodic instruction on working memory recall in individuals with Autism Spectrum Disorder (ASD). The purpose of this study was to examine the effects of instructor gender and visual and auditory melodic instruction on working memory in individuals with ASD. Participants (n = 38 individuals with ASD and n = 18 neurotypical [NT] university students) viewed or listened to four melodic sequences of seven randomized monosyllabic words sung by female and male instructors. To assess working memory, participants’ tasks were to sequentially recall the paired information presented within each condition. There was no significant within-group difference between both the male and female instructor conditions or the visual + auditory or auditory only melodic instruction. Although not significant, participants tended to have slightly higher mean recall for the male instructor with visual + auditory stimuli condition and lower mean recall for the female instructor with auditory only stimuli condition. There was a significant between-group difference with the NT group having greater recall accuracy than the ASD group. Regardless of group or condition, participants tended to have greater recall accuracy at primary and recency serial positions. As individuals with ASD may have unique learning challenges, information paired with music may be delivered in multi-sensory ways to increase the likelihood of recall and subsequent learning. Implications for clinical practice, limitations of the study, and suggestions for future research are provided.